Modificaciones del plaquetograma en pacientes diabéticos del Centro de Salud de Motupe de la ciudad de Loja - Collaguazo Apolo, Cristian Gustavo (2022)
Actually diabetes continues to be a public health problem given its high rates of morbidity and mortality, this metabolic disease causes a hyperglycemic internal environment favoring platelet hyperreactivity and its subsequent alterations, seeing involved in the development of micro and macrovascular complications. This study aimed to stratify the diabetic group of the Motupe Health Center according to age and sex, in addition; to compare the plateletogram indices measurement between the diabetic group and the control group; and find the most frequent platelet alteration in the diabetic group. The study design is quantitative of non-experimental type and correlational cross section. The sample was constituted of 100 diabetics and 100 patients who presented a fasting glycemia between 70 - 100 mg / dl as a control group, using non-probabilistic sampling. Plateletogram determination was performed by an automated analyzer, the platelet count was validated supported by the estimated count by the indirect method in peripheral blood smears and in turn observe the platelet alterations. Finding that, of the diabetic group, 90% had an age between 50 and 80 years with the predominance of women (69%) over men (31%). El VPM, PDW and P– LCR were statistically different (p<0.05) between the diabetic group and the control group, presenting higher values in diabetics, they presented platelet alterations in the blood smear, being frequent platelet anisocytosis accompanied by macroplatelets. Reaching the conclusions that, most of the diabetic group were patients between middle and old age with a predominance of women; they also had higher averages of MPV, PDW, and P–LCR compared with the control group; the same values that were reflected in peripheral blood smear, since the most frequent platelet alterations were the presence of anisocytosis and macroplatelets